Influence of high fidelity structural models on the predicted mass of aircraft wing using design optimization - Dababneh, Odeh; Kipouros, Timoleon (Elsevier, 2018)
This paper explores the necessary and appropriate level of detail that is required to describe the structural geometry of aircraft wings accurately enough to predict the mass of the main load-carrying wing structure to an acceptable level of accuracy. Four different models of increasing structural fidelity are used to describe the wingbox structure of a realistic real-world aircraft wing. The wingbox of the NASA Common Research Model served as a test model for exploring and analyzing the trade-off between the granularity level of the wingbox geometry description under consideration and the computational resources necessary to achieve the required degree of accuracy. The mass of metallic and composite wingbox configurations was calculated via finite element analysis and design optimization techniques. The results provided an insight into the competence of certain wingbox models in predicting the mass of the metallic and composite primary wing structures to an acceptable level of accuracy, and in demonstrating the relative merits of the wingbox structural complexity and the computational time and input efforts for achieving the required level of accuracy.
Keywords: Wing mass; Primary wing structures; High-fidelity models; Finite element; Optimization